Non-contact human identification through radar signals using convolutional neural networks across multiple physiological scenarios - Foronda-Pascual, Daniel; Camara, Carmen; Peris-Lopez, Pedro (Frontiers in Digital Health, 2025)
IntroductionIn recent years, contactless identification methods have gained prominence in enhancing security and user convenience. Radar-based identification is emerging as a promising solution due to its ability to perform non-intrusive, seamless, and hygienic identification without physical contact or reliance on optical sensors. However, being a relatively new technology, research in this domain remains limited. This study investigates the feasibility of secure subject identification using heart dynamics acquired through a continuous wave radar. Unlike previous studies, our work explores identification across multiple physiological scenarios, representing, to the best of our knowledge, the first such exploration.MethodsWe propose and compare two identification methods in a controlled Resting scenario: a traditional machine learning pipeline and a deep learning-based approach. The latter consists of using a Convolutional Neural Network (CNN) to extract features from scalograms, followed by a Support Vector Classifier (SVC) for final classification. We further assess the generalizability of the system in multiple scenarios, evaluating performance both when the physiological state is known and when it is not.ResultsIn the Resting scenario, the deep learning-based method outperformed the traditional pipeline, achieving 97.70% accuracy. When extending the identification task to various physiological scenarios, 82% of predictions exceeded scenario-specific confidence thresholds, achieving 98.6% accuracy within this high-confidence subset.DiscussionOur findings suggest that radar-based identification systems can match the performance of established biometric methods such as electrocardiography (ECG) or photoplethysmography (PPG), while offering the additional benefit of being contactless. This demonstrates the potential of radar heart signal analysis as a reliable and practical solution for secure human identification across diverse conditions.